ANALISIS PENGARUH HARGA PRODUK, BIAYA PROMOSI, dan HARGA EKSPOR BATUBARA TERHADAP VOLUME PENJUALAN HYDRAULIC EXCAVATOR PC200-8M0 - Erika Nabila Imanesti; Winarto Winarto; Noor Suroija (JOBS (Jurnal Of Business Studies), 2018)
The purposes of this research were to analyze the influence of product price, promotion expense, and coal export price on Hydraulic Excavator PC200-8M0 sales volume by simultaneously and also attempt to how many contribution of each variabel. This research used secondary data in the form of time series data monthly, starting from January 2015 until December 2017. Analysis methods of this research is multiple linier regression wich completed with classic assumption test (normality, heteroscedasticity, multicollinearity, autocollinearity and linearity test) and goodness of fit model test (coefficient determination, t test, and F test). The classic assumption test shows that there is no trouble with all of those variables. The result of structural equation is Sales Volume = 4.707.869.796 – 8,022 Product Price + 86,828 Promotion Expense + 10.454,693 Coal Export Price. The result of F test shows that there is a simultaneous influence among product price, promotion expense, and coal export price on sales volume of Hydraulic Excavator PC200-8M0 Based on the coefficient determination of adjusted R square, the product price, promotion expense and coal export price given 74,9% influence while 25,1% is explained by other variables outside this research model.